Bioimaging of copper deposition in Wilson's diseases mouse liver by laser ablation inductively coupled plasma mass spectrometry imaging (LA-ICP-MSI) - Pornwilard, M.-M.; Merle, Uta; Weiskirchen, Ralf; Becker, J. Sabine (International journal of mass spectrometry, 2013)
Unbalance of metals play an important role in the development of liver diseases. Wilson's disease for example is an autosomal recessive disorder in which the liver does not release copper into bile and resulting metal buildup leads to organ damage and liver failure. Laser ablation inductively coupled plasma mass spectrometry imaging (LA-ICP-MSI) is an established analytical technique for the determination of trace metals in biological tissue. This work demonstrates a new application of LA-ICP-MSI of trace metal imaging (Mn, Fe, Cu, and Zn) to study Wilson's disease in mouse liver tissue (vs. control sections). The quantification of tissue trace metals was performed using in-house produced tissue standards from murine brain with well-defined element concentrations. The results show that the average concentrations of Mn in control (0.7μgg−1) and Wilson's disease liver samples (0.6μgg−1) were not different. In contrast, Fe, Cu, and Zn in Wilson's disease liver samples (80μgg−1 for Fe, 143μgg−1 for Cu, and 32μgg−1 for Zn) were found significantly higher than in control tissue samples (41μgg−1 for Fe, 4μgg−1 for Cu, and 18μgg−1 for Zn).